Goulet, H. 2020: Nearctic Tenthredo: a monograph of the verticalis and prosopa groups (Hymenoptera: Tenthredinidae). – In: Nova Supplementa Entomologica, Müncheberg 26: 1–178: Corrections - Goulet, Henri (Beiträge zur Entomologie = Contributions to Entomology, 2020)
-